Capacity building and transfer of technology competencies: an analysis of Indonesian and Malaysian agricultural extensionists’ work performance - Prajanti, Sucihatiningsih; Utami, Sri; Hamsan, Hanina Halimatusaadiah; Mohd Salleh, Lailawati; Mohd Sail, Rahim (Universiti Putra Malaysia Press, 2020)
Capacity building and transfer of technology (ToT) competencies are two important job requirements of extensionists which are performed to benefit client groups in the form of adopting new technology/idea/practice for higher productivity and improved quality of products produced. Capacity building, in this study, focuses on human resource development (HRD) variables of leadership development, problem solving and decision-making skills (the hidden competencies). On the other hand, ToT variables comprised new technology/idea/practice (the visible competencies). The study employed a survey design using questionnaires to collect data from respondents in Central Java, Indonesia and North and Central Terengganu, Malaysia. The main objective of the study was to determine the relationships between ToT and HRD variables with extensionists’ job performance. Level of performance of extensionists in ToT and HRD tasks variables were similar in Indonesia and Malaysia, ranging from as low as 5% to as high as 60%. All ToT and HRD variables were positive and significantly related to extensionists’ job performance in Indonesia and Malaysia. The findings of the present study were not conclusive enough to indicate that agricultural extensionists preferred to carry out ToT task over HRD task. This was true for the Indonesian and Malaysian data when the two situations were compared. It is suggested that the mixed methods of quantitative and qualitative strategies should be used for future studies to reflect actual agricultural extensionists’ job performance.